Pengaruh Lingkungan Sekolah terhadap Motivasi Belajar Siswa Kelas IX SMP Swasta IMELDA Medan - Putri, Fadira; Araudha, Nadra; Nasution, Sasqia Salsa Zahra (Program Studi Bimbingan dan Konseling, Universitas Negeri Jakarta, 2024)
This study aims to determine the influence of the school environment on the learning motivation of grade IX students of Imelda Medan Private Junior High School. This study used a quantitative research approach. The population used in this study was class IX of Imelda Medan Private Junior High School consisting of 88 students. The sample in this study was taken, amounting to 15 students of class IX-B, the research instrument used was a questionnaire with the Simple Random Sampling technique. The results of the study used Descriptive statistical analysis, the average score of the school environment is 111. 93 are in the very high category and learning motivation with a total of 122.67 is in the very motivated category. Analysis of the prerequisites of the school environment normality test results and learning motivation of 0.200 >0.05 (normally distributed), the results of the hypothesis test showed a GIS value of 0.000 with GIS criteria (0.000) < α (0.05).Based on the results of the linearity test is 0.534>0.05 based on the results of these data, there are The linear relationship of the school environment to learning motivation. A high regression value or (R) effect of 0.903, the result of the coefficient of determination (R2) is 0.815. The conclusion in this study is that there is an influence of the school environment on the learning motivation of grade IX-B students of Imelda Medan Private Junior High School.